Solvent extraction of trivalent indium from succinate solution by 2-octylaminopyridine in chloroform - Mahamuni, Sandip V.; Kolekar, S. S.; Wadgaonkar, P. P.; Anuse, Mansing A. (Journal of the Iranian Chemical Society, 2009)
Extraction processes of indium(III) with 2-octylaminopyridine (2-OAP) from media of various complexing ability, succinate and salicylate, in chloroform have been elucidated. The ion-pair complex has also quantitative extraction in xylene and 1,2-dichloroethane. Indium(III) from organic phase was stripped with 1.0 M hydrochloric acid and determined complexometrically with EDTA. The stoichiometry of the extracted species was found out on the basis of slope analysis. The extraction of indium(III) proceeds by an anion exchange mechanism and the extracted species is [RR'NH(2)(+)In(succinate)(2)(-)]((org)). Temperature dependence of the extraction equilibrium constant was also examined to estimate the apparent thermodynamic functions (Delta H, Delta G and Delta S) for extraction reaction. It is possible to separate indium(III) from Zn(II), Cd(II), Pb(II), Hg(II), Bi(III), Tl(I), Tl(III), Ga(III), Al(III), Te(IV), Se(IV), Sb(III), Fe(III) and Sn(IV). The method is simple, rapid and reproducible and can be used to determine the indium from samples like alloys.
Keywords: 2-OAP; Binary separations; Indium(III); liquid-liquid extraction; Sodium succinate